Stacked graphene with nanoscale wrinkles supports osteogenic differentiation of human adipose-derived stromal cells. (4th March 2021) - Park, Jong Bo; Ahn, Ji Yeon; Yang, Woo Sub; Park, Seong Chae; Jung, Young Jin; Lee, Myungook; Hong, Byung Hee; Lim, Jeong Mook
Abstract: Based on the concept that microenvironment and physical stimuli regulate the cell behaviors like proliferation, migration, and differentiation, this study was conducted to investigate whether nanoscale spacing by stacked graphene film affect osteogenic differentiation of human adipose-derived mesenchymal stromal cells (hADSCs). The graphene films were synthesized by a chemical vapor deposition method, followed by etching and rinsing process to fabricate single or 3-, 5-, and 7-multilayers. The height and width of wrinkles of the graphene were confirmed by SEM and atomic force microscopy (AFM), ranging from 1.5 to 12.5 nm and from 30 to 100 nm, respectively. Osteogenic differentiation was significantly ( p < 0.0001) promoted as the stacking layer increased. Immunofluorescent imaging and osteogenesis-related gene expression showed which increment was saturated from three layers. The calcium deposits and expression of osteogenesis-related genes ( Runt-related transcription factor 2 and Osteocalcin ) were highest in the three layers. In the hADSCs cultured on the three layers, the intensity of protein expression levels of filamentous actin (F-actin) was significantly increased ( p = 0.0319) and focal adhesion kinase/extracellular signal-regulated kinase signal related genes were concomitantly activated. These results demonstrated that multilayer-stacked graphene creating nanoscale spaces promotes calcium deposit and cytoskeletal integrity in hADSC-related, in vitro -osteogenesis.